Understanding Indonesia’s Response to Russia’s war in Ukraine: - Dharmaputra, Radityo (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2022)
A Preliminary Analysis of the Discursive Landscape